Market participation of small-scale rice farmers in Eastern Bolivia - Lopera, Diana Carolina; Gonzalez, Carolina; Martinez, Jose M. (Cambridge University Press, 2023)
Using a double-hurdle approach, we assess factors associated with the extent of participation in the rice market with data for small-scale farmers drawn from a nationally representative dataset. The results suggest that larger endowments and assets, animal farming and commercialization, and alternative off-farm income make farmers less likely to participate. Conversely, having access to credit, larger farm sizes, and being part of a farmers’ association all increase the likelihood of participation. Farms with better technological resources are also those with higher sales volumes. Further understanding market participation dynamics should prove useful for deriving evidence-based policy recommendations to strengthen this Bolivian sector.